Palliative radiotherapy in cancers of female genital tract: Outcomes and prognostic factors. (October 2022) - Kombathula, Sri Harsha; Cree, Anthea; Joshi, Priya V.; Akturk, Nesrin; Barraclough, Lisa H.; Haslett, Kate; Choudhury, Ananya; Hoskin, Peter
Highlights: Outcome in the largest series of palliative gynaecological pelvic radiotherapy. Overall 80.4% symptom response rate. Toxicity low: ≥Grade v3 GI 2.2% and urinary 3.8%. 1 year OS was 25.1% and the median survival was 5.9 months. Abstract: Background and purpose: Metastatic and incurable cancers of the gynaecological tract (FGTC) represent a major global health burden. Systemic treatment has modest efficacy and radiotherapy is often used for local symptoms. This study combines experience from two large UK centres in palliative radiotherapy for gynaecological cancers. Materials and methods : Pooled data from two major centres was analysed. Advanced FGTC patients who received at least one fraction of palliative radiotherapy to the pelvis between 2013 and 2018 were included. Data collected included demographic and tumour details, radiotherapy dose fractionation and details of previous and subsequent treatment. Response was defined in terms of toxicity, symptomatic response and survival. Comorbidities were recorded using a modified ACE 27 score which is adjusted for the presence of uncontrolled FGTC in all the patients. Results: A total of 184 patients were included for treatment response and toxicity; survival data was available for 165 patients. Subjective response in pre-radiotherapy symptoms was documented in 80.4%. Grade 3 or worse gastrointestinal, urinary and other (vomiting, fatigue, pain) toxicity incidence was 2.2%, 3.8%, and 2.7% respectively. No statistically significant correlation between the prescribed EQD210 and symptom control or toxicity was seen. 1 year overall survival was 25.1% (median 5.9 months). Absent distant metastases, completion of the intended course of radiotherapy, response to radiotherapy, and receipt of further lines of treatment were independent prognostic factors. Conclusion: Palliative radiotherapy is effective for symptoms of advanced FGTC with low toxicity. The absence of a dose response argues for short low dose palliative radiotherapy schedules to be used.